A multi-institutional analysis of a general pelvis continuous Hounsfield unit synthetic CT software for radiotherapy - Yu Victoria Y.; Keyriläinen Jani; Suilamo Sami; Beslimane Ilyes; Dresner Alex; Halkola Aleksi; Van der Heide Uulke A.; Tyagi Neelam (WILEY, 2022)
Purpose To validate a synthetic computed tomography (sCT) software with continuous HUs and large field-of-view (FOV) coverage for magnetic resonance imaging (MRI)-only workflow of general pelvis anatomy in radiotherapy (RT).Methods An sCT software for general pelvis anatomy (prostate, rectum, and female pelvis) has been developed by Philips Healthcare and includes continuous HUs assignment along with large FOV coverage. General pelvis sCTs were generated using a two-stack T1-weighted mDixon fast-field echo (FFE) sequence with a superior-inferior coverage of 36 cm. Seventy-seven prostate, 43 rectum, and 27 gynecological cases were scanned by three different institutions. mDixon image quality and sCTs were evaluated for soft tissue contrast by using a confidence level scale from 1 to 5 for bladder, prostate/rectum interface, mesorectum, and fiducial maker visibility. Dosimetric comparison was performed by recalculating the RT plans on the sCT after rigid registration. For 12 randomly selected cases, the mean absolute error (MAE) between sCT and CT was calculated to evaluate HU similarity, and the Pearson correlation coefficients (PCC) between the CT- and sCT-generated digitally reconstructed radiographs (DRRs) were obtained for quantitative comparison. To examine geometric accuracy of sCT as a reference for cone beam CT (CBCT), the difference between bone-based alignment of CBCT to CT and CBCT to sCT was obtained for 19 online-acquired CBCTs from three patients.Results Two-stack mDixon scans with large FOV did not show any image inhomogeneity or fat-water swap artifact. Fiducials, Foley catheter, and even rectal spacer were visible as dark signal on the sCT. Average visibility confidence level (average +/- standard deviation) on the sCT was 5.0 +/- 0.0, 4.6 +/- 0.5, 3.8 +/- 0.4, and 4.0 +/- 1.1 for bladder, prostate/rectum interface, mesorectum and fiducial markers. Dosimetric accuracy showed on average < 1% difference with the CT-based plans for target and normal structures. The MAE of bone and soft tissue between the sCT and CT are 120.9 +/- 15.4 HU, 33.4 +/- 4.1 HU, respectively. Average PCC of all evaluated DRR pairs was 0.975. The average offset between CT and sCT as reference was (LR, AP, SI) = (0.19 +/- 0.35, 0.14 +/- 0.60, 0.44 +/- 0.54) mm.Conclusions The continuous HU sCT software-generated realistic sCTs and DRRs to enable MRI-only planning for general pelvis anatomy.